Teaching: more than just lecturing - Roettger, C.; Roettger, L.; Walugembe, F. (Journal of University Teaching and Learning Practice, 2007)
This study focused on effective teaching strategies for university professors. Theresearchers studied the relationship between teaching effectiveness and thedynamics of student demographics. An examination of the changes in thecomposition of the college population over the last few decades, based onstatistical data, as well as an overview of theories of teaching and learningpublished in professional books and journals in both K-12 and Higher Education,provided the framework for an assessment of the effectiveness of variousapproaches to teaching. The final recommendations are based on theconclusions resulting from a comprehensive analysis of various research studies.